Estudo Técnico Do Sistema De Abastecimento De Água Do Município De Rio Sono - TO - Almeida, Bruno Oliveira (Universidade Federal do Tocantins, 2022)
The importance of basic sanitation begins with its influence on health, quality of life and on the development of society as a whole. The treatment and supply of water is essential to maintain the quality of life of populations, since in addition to being essential to the human organism, it is the main means of proliferation of endemic diseases. This study aims to present the diagnosis of the current water supply system in the city of Rio Sono - TO in the urban area, and from that, propose alternatives to solve the problems identified in relation to the water supply system. To carry out the study, a population projection was made for a 20-year horizon. The primary data were obtained through a technical visit to the city, in addition, bibliographic research was also carried out, which served as secondary data for the study. The result presented in this work shows that the current production of the water supply system is able to meet the current population and the projected one for a 20-year horizon. It was possible to verify that it will not be necessary to implement new reservoirs, as the current ones with a capacity of 200 m3 are able to supply the demand. A problem identified was the increase in the rate of losses due to water distribution in recent years, despite being below the averages of the municipalities in the state and even the average in the northern region, the municipality even presented 29.09% of loss in the year from 2019, while the average from 2016 to 2018 was 22.00%, after identifying the causes of these losses, alternatives were proposed to reduce this index. Another problem identified was related to the extension of the water distribution network, currently with 27.85 km, will only be able to meet the projected population until the year 2022, being necessary to expand the extension of the network.